Gastrostomy Tube Placement by Radiological Methods for Older Patients Requiring Enteral Nutrition: Not to be Forgotten - Hermush, Vered; Berner, Yitshal; Katz, Yael; Kunin, Yanina; Krasniansky, Irena; Schwartz, Yael; Mimran Nahon, Debbie; Elizariev, Ana; Mendelson, Gad (Frontiers in Medicine, 2018)
Background: The use of gastrostomy tubes for long-term nutritional support in older patients is frequent. Percutaneous gastrostomy tube placement may be performed using various techniques, including endoscopic, surgical, and radiologically-guided methods. While percutaneous endoscopic gastrostomy (PEG) placement is the most widely used and accepted approach, experience with the use of percutaneous radiological gastrostomy (PRG) is more limited. Objective: To evaluate the safety and short-term outcomes of PRG in older patients requiring long-term enteral feeding. Method: We performed a prospective study involving all patients aged 65 years and older who underwent PRG insertion at the Laniado hospital over a period of two years. Adverse events related to the gastrostomy tube insertion were recorded over a period of three months following the procedure. Results: A total of 58 patients were included with a mean age of 78.1 years, and 48% were women. The most frequent indications for enteral feeding were stroke (47%) and dementia (41%). The technical success rate was 100% with no immediate procedure-related mortality or morbidity. One-month mortality was 3%, and overall mortality at 3-month follow-up was 16%. Complications were reported in 39 (67%) of patients, with 17 (29%) experiencing more than 1 complication. While most complications (88%) were minor, major complications occurred in 19 (33%) of the patients. Peritonitis was the cause of death in 2 patients, and tube dislodgment occurred in 17 subjects. During the follow-up period 17 (29%) of patients were re-admitted to hospital, with the cause for re-hospitalization being unrelated to the PRG in half of the cases. Neither bleeding nor deep wound infection was detected in the study group. Conclusions: PRG is relatively safe and effective for gastrostomy placement in older patients, and this technique may be of value in patients with oral infections and those receiving anti-thrombotic therapy.